2015
DOI: 10.1038/ncomms10034
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking in drop bouncing on curved surfaces

Abstract: The impact of liquid drops on solid surfaces is ubiquitous in nature, and of practical importance in many industrial processes. A drop hitting a flat surface retains a circular symmetry throughout the impact process. Here we show that a drop impinging on Echevaria leaves exhibits asymmetric bouncing dynamics with distinct spreading and retraction along two perpendicular directions. This is a direct consequence of the cylindrical leaves that have a convex/concave architecture of size comparable to the drop. Sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
283
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 383 publications
(296 citation statements)
references
References 47 publications
12
283
0
1
Order By: Relevance
“…A spectacular reduction in contact time by factor of four was reported. Further experimental studies of similar macro-textures can be found in [12,18]. Although pancake bouncing was shown to reduce the contact time significantly, questions remain regarding the physics behind the phenomenon including the role played by surface energy, viscous dissipation and influence of air pockets that might be trapped between the droplet and the surface texture.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A spectacular reduction in contact time by factor of four was reported. Further experimental studies of similar macro-textures can be found in [12,18]. Although pancake bouncing was shown to reduce the contact time significantly, questions remain regarding the physics behind the phenomenon including the role played by surface energy, viscous dissipation and influence of air pockets that might be trapped between the droplet and the surface texture.…”
Section: Introductionmentioning
confidence: 99%
“…Minimization of contact time is a central point in a rational design of hierarchically structured surfaces and has been the focus of recent studies [6,7,12,18,19,32,37,38]. Richard, Clanet, and Quéré [32] found that the conventional mechanism of rebound on macroscopically flat superhydrophobic surfaces (impact-spread-recoil-rebound, [28, 31, 32, 43]) scales universally with the inertia-capillarity time,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have recently shown that the drop-substrate contact time is reduced if the bouncing is not axisymmetric [20][21][22][23] . Non-axisymmetric bouncing may result from an asymmetry in the initial conditions, such as different initial momenta along the a and b directions or a non-axisymmetric drop shape at the collision, or from anisotropy of the physical process of interaction of the drop with the substrate, such as anisotropic surface drag.…”
Section: Non-axisymmetric Bouncingmentioning
confidence: 99%
“…Examples include micro-scale ridges on a flat surface 20 , superhydrophobic stripes 21 , cylindrical substrates 22 , and wires laid upon surfaces 23 . These experiments and simulations showed that inducing non-axisymmetric bouncing modes reduces the contact time of a drop on a surface below that found for axisymmetric collisions.…”
Section: Introductionmentioning
confidence: 99%